2014
DOI: 10.1002/bip.22448
|View full text |Cite
|
Sign up to set email alerts
|

Shape readout of AT‐rich DNA by carbohydrates

Abstract: Gene expression can be altered by small molecules that target DNA; sequence as well as shape selectivities are both extremely important for DNA recognition by intercalating and groove-binding ligands. We have characterized a carbohydrate scaffold (1) exhibiting DNA “shape readout” properties. Thermodynamic studies with 1 and model duplex DNAs demonstrate the molecule's high affinity and selectivity towards B* form (continuous AT-rich) DNA. Isothermal Titration Calorimetry (ITC), Circular Dichroism (CD) titrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…The assay was validated for A-site binding by determining the relative displacement of known aminoglycosides with previously reported results; 40 additionally, the assay has been successfully employed in screening of a neomycin dimer compound library. 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The assay was validated for A-site binding by determining the relative displacement of known aminoglycosides with previously reported results; 40 additionally, the assay has been successfully employed in screening of a neomycin dimer compound library. 18 …”
Section: Resultsmentioning
confidence: 99%
“…The results of the assay were well correlated with antibacterial activity of bacterial strains determined by MIC calculations. 18 …”
mentioning
confidence: 99%
“…Hexa- N -Boc deoxy-neomycin-5″-amine with short and long (Figure 1) linkers were synthesized from commercially available neomycin sulphate using previously published methods. 13, 18, 19, 21, 22 The diisothiocyanate linkers used in the synthesis of neomycin dimers were prepared by reacting commercially available diamines with TCDP (1,1′-thiocarbonyldi-2(1 H )-pyridone) in almost quantitative yields (see supplementary information Table S1). The Hexa- N -Boc deoxy-neomycin-5″-amines were then reacted with diisothiocyanates and diisocyanates in the presence of pyridine (dry) and DMAP (catalytic amounts) for 12 hours at room temperature to produce the Boc protected neomycin dimers with various linker lengths (DPA71–DPA80, see supporting information Scheme S1).…”
Section: Resultsmentioning
confidence: 99%
“…The ITC studies were performed at pH = 5.5 to ensure that the dimers were substantially protonated (lowest pK a for an amine group of neomycin = 5.91). 19 The following observations were noted from the thermodynamic characterization. (1) Similar to our earlier reported work, neomycin dimers with linker length L=12 to 22 exhibit two sets of binding sites, in which the first is predominantly entropically driven, with a binding stoichiometry of 1:1 (neomycin dimer:DNA) while the second is enthalpically driven with a binding stoichiometry of ~3:1 (neomycin dimer:DNA).…”
Section: Resultsmentioning
confidence: 99%
“…18 ) binds to short oligonucleotides (12 mer) with 1:1 ligand to DNA duplex stoichiometry and show a binding site size of 11–12 base pairs with the polymeric DNA. A complete thermodynamic study of neomycin dimer 115 binding to a B-DNA sequence revealed that the first binding event (the high affinity site) is entropically driven and that the ionic strength dependence of the binding is highly dependent on the electrolytic contribution [ 194 ]. The neomycin dimers also displayed length dependent shape recognition of the B-DNA [ 195 ].…”
Section: Reviewmentioning
confidence: 99%